American poetry since 1945 A critical survey - Stepanchev, Stephen (Harper & Row, 1965)
Also includes material on Charles Olson, Robert Duncan, Robert Creeley, Denise Levertov, James Wright, Robert Bly, John Ashbury, James Dickey, Alan Dugan, LeRoi Jones, Louis Simpson, William Stafford, and May Swenson.